2022
DOI: 10.1186/s12882-022-02821-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in kidney transplant recipients with COVID‐19: a single centre experience and case–control study

Abstract: Background COVID-19 infection is considered to cause high mortality in kidney transplant recipients (KTR). Old age, comorbidities and acute kidney injury are known risk factors for increased mortality in KTR. Nevertheless, mortality rates have varied across different regions. Differences in age, comorbidities and varying standards of care across geographies may explain some variations. However, it is still unclear whether post-transplant duration, induction therapy, antirejection therapy and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…From the results of the European Renal Association COVID-19 Database (ERACODA) database, most of the enrolled 305 RTRs with COVID-19 were males with a mean age of 60 ± 13 years ( 18 ). The single center also showed that COVID-19 infection in this RTR group affected men more than women ( 19 ). In our study, the two groups in the gender category had statistically comparative differences, and there was a preponderance of males in both groups.…”
Section: Discussionmentioning
confidence: 83%
“…From the results of the European Renal Association COVID-19 Database (ERACODA) database, most of the enrolled 305 RTRs with COVID-19 were males with a mean age of 60 ± 13 years ( 18 ). The single center also showed that COVID-19 infection in this RTR group affected men more than women ( 19 ). In our study, the two groups in the gender category had statistically comparative differences, and there was a preponderance of males in both groups.…”
Section: Discussionmentioning
confidence: 83%
“…Llama la atención la proporción de pacientes que inició con diarrea como síntoma principal del cuadro clínico (34%), este fenómeno ya se había descrito en la literatura y se había postulado como factor con potencial riesgo para mortalidad 18 ; sin embargo en nuestra experiencia no fue posible establecer algún tipo de asociación con significancia estadística o clínica.…”
Section: Discussionunclassified
“…KTRs have a poorer prognosis than the general population with regard to COVID-19 infections. Early data revealed that the mortality rate of KTRs infected with COVID-19 ranges from 20 to 32% [1,[3][4][5], according to data from WHO, the infection fatality ratio for COVID-19 in the general population is estimated to converge at approximately 0.5 to 1% [6].…”
Section: Discussionmentioning
confidence: 99%
“…(4) The SARS-CoV-2 strain is identified as Omicron variant by Sanger sequence or BALF-mNGS. (5) Ethnicity: Asian Chinese Han population.…”
Section: Study Subjectsmentioning
confidence: 99%